2020
DOI: 10.3390/jcm9072261
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Thermo-Sensitive Sol–Gel Anti-Adhesion Agent after Gynecologic Surgery

Abstract: Postoperative abdominal adhesions can lead to several adverse consequences such as pelvic pain, bowel obstruction, and infertility. We aimed to explore the anti-adhesion efficacy and safety of a thermo-sensitive sol–gel agent in patients who receive abdominopelvic surgery for benign gynecologic disease. This study was a randomized, controlled, single-blind clinical trial of women undergoing benign gynecologic surgery between January 2017 and December 2017. The patients were randomly assigned to three groups wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Similar to several previous studies, this study confirmed that Mediclore could be used safely [ 9 10 11 12 ]. Inflammatory assessment by questionnaire confirmed the absence of Mediclore-associated inflammatory response.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to several previous studies, this study confirmed that Mediclore could be used safely [ 9 10 11 12 ]. Inflammatory assessment by questionnaire confirmed the absence of Mediclore-associated inflammatory response.…”
Section: Discussionsupporting
confidence: 91%
“…Mediclore acts as an external barrier to prevent adhesion until absorbed for approximately 20 days. Anti-adhesive and antibacterial effects of Mediclore have been reported in various studies [ 9 10 11 12 21 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a randomized, controlled, single-blinded clinical trial conducted by Kim et al [93], the subjects were women who underwent benign gynecological surgery from January to December 2017. Patients were randomly divided (1:1:1) into a test group (received thermosensitive hydrogel treatment), control group (nontreatment), or a comparator group (received 4% icodextrin treatment), with four weeks of follow-up.…”
Section: Prevention Of Postoperative Adhesionmentioning
confidence: 99%